Intrusion detection systems with deep learning: A systematic mapping study - Ösken, Sinem; Yıldırım, Ecen Nur; BAYDOĞMUŞ, GÖZDE KARATAŞ; CUHACI, LEVENT (My University, 2019)
In this study, a systematic mapping study was conducted to systematically evaluate publications on Intrusion Detection Systems with Deep Learning. 6088 papers have been examined by using systematic mapping method to evaluate the publications related to this paper, which have been used increasingly in the Intrusion Detection Systems. The goal of our study is to determine which deep learning algorithms were used mostly in the algortihms, which criteria were taken into account for selecting the preferred deep learning algorithm, and the most searched topics of intrusion detection with deep learning algorithm model. Scientific studies published in the last 10 years have been studied in the IEEE Explorer, ACM Digital Library, Science Direct, Scopus and Wiley databases.
Keywords: Deep Learning; Intrusion Detection; Systematic Mapping Study; Derin Öğrenme; İzinsiz Giriş Tespiti; Sistematik Harita Çalışması